KAWASAN KARST TUBAN: SALAH SATU SISA KEHIDUPAN MANUSIA MASA LALU - Rr. Triwurjani (BRIN, 2001)
From the available data, it can be explained that the Tuban Karst area, especially Semanding, Montong, Plumpang and Rengel Districts, has played a role in past human life, the survival of the caves inhabitants of these regions is supported by the surrounding natural resources consisting of plains and sea. Thus, it can be said that the Tuban area is rich in archaeological remains, although the existing finds consist mostly of surface finds, unevenly distributed in this area. This is largely due to the large-scale mining of limestone which lasts a long time.